Eksistensi Bale Beleq dalam Mempertahankan Adat dan Budaya Masyarakat Jerowaru Lombok Timur - Ardi Wire Sentane; Zidni Zidni; Suhupawati Suhupawati (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
This study aims to determine the existence of Bale Beleq and efforts to maintain customs and culture in the Bale Beleq celebration in Wakan Village, Jerowaru District, East Lombok Regency. The research uses a qualitative approach with a phenomenological research type. Data collection was conducted through observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model consisting of data reduction, data display, and conclusion drawing. The results showed that Bale Beleq still exists and is visited by various groups of people who want to make pilgrimages and carry out traditional rituals. Customs continue to be carried out according to the traditions of predecessors, while community culture is maintained through values of mutual cooperation, friendship, togetherness, sharing, and shared responsibility. Efforts to maintain the existence of Bale Beleq are carried out by instilling positive values contained in the celebration, namely monotheism values, piety values, and tolerance values. These values become social adhesive that prevents differences of opinion among the community. This study recommends systematic documentation and cultural education for the younger generation to ensure the sustainability of the Bale Beleq tradition amidst modernization.